THEORETICAL AND CONCEPTUAL PRINCIPLES OF FORMING REGIONAL STRUCTURAL ECONOMIC POLICY FOR ENTREPRENEURSHIP DEVELOPMENT - MULSKA, Olha; GRES, Arsen (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study focuses on the issues of forming and implementing effective regional policy, focused on the sustainable balanced development of the region as a socio-economic system. It is proven that the stable long-term development of the region is closely correlated with the establishment of structural balances in its economy and social system, among the main characteristics of which is the system of functioning and development of the entrepreneurial sector of the regional economy. That is why the purpose of the study is to generalize the theoretical and conceptual principles of the formation of regional structural economic policy for the development of entrepreneurship. The clarification of the conceptual and substantive characteristics of the goal of regional structural policy is facilitated by understanding its target guidelines. It is proven that the goals of structural policy should be oriented towards overcoming existing disparities that hinder the socio-economic development of the region and its territories; achieving the planned characteristics of the structure of the regional economy; formation of resource support for institutional changes and structural reforms; strengthening technological competitiveness and ensuring smart specialization of the regional economy; leveling spatial and structural imbalances of regional development; establishment of a transparent competitive environment in the markets; strengthening the resilience, stability and economic security of the regional economy. A system of elements of regional structural policy has been defined, among which the leading ones are the goal, system of goals, principles, forms and types of implementation, mechanisms, tools, and means of control. The goal of regional structural policy is defined as achieving rational structural relations according to the leading characteristics of balancing the regional economic system – aspects of spatial and territorial development, sectoral changes, reproduction, innovative and technological progress, foreign economic activity, institutional changes, etc.
Keywords: region; regional policy; regional economy; entrepreneurship; entrepreneurial sector; structural economic policy; structural changes and reforms